Coastal Erosion and Sedimentation in Khums City, Libya using Sentinel-1A Technology: An Environmental Study - Dawi Ageel (AlQalam Journal of Medical and Applied Sciences, 2025)
The majority of coastal regions worldwide are currently experiencing erosion processes, which are frequently brought on by modifications in the sediment balance brought on by both natural and man-made sources. Numerous Mediterranean locations, including the study area, are affected by this problem. The coastal area’s erosion and sedimentation rates are not constant, and the pace of change is not uniform and varies widely, according to this study. Using Sentinal-1A remotely sensed satellite data sets, the study examined coastline changes from 2000 to 2021 and found such disparities in shoreline changes throughout the previous 21 years. The rates of erosion and accumulation were also calculated. Using many profiles, each of which expressed a rate of coastal erosion or sedimentation, the Digital coastline Analysis System (DSAS) tool was utilized to determine patterns in coastline change. According to the findings, the research site’s west had a high rate of erosion, while its east had a high rate of sedimentation. In the center Khums area, both rates were equal. According to the results, sedimentation rates were higher than those of the study areas, with the exception of Basis Island, where erosion rates were higher. The rates calculated in this study and the classification of the study site’s beaches may be very helpful in determining the cumulative impact and erosion risks of the coastal areas under study, as well as in developing sustainable development plans for them and raising awareness in the most vulnerable areas. تشهد غالبية المناطق الساحلية في جميع أنحاء العالم حاليًا عمليات تآكل، والتي تحدث غالبًا بسبب التعديلات في توازن الرواسب الناجمة عن مصادر طبيعية وبشرية. تتأثر العديد من المواقع المتوسطية، بما في ذلك منطقة الدراسة، بهذه المشكلة. وفقًا لهذه الدراسة، فإن معدلات التآكل والترسيب في المنطقة الساحلية ليست ثابتة، ووتيرة التغيير ليست موحدة وتختلف على نطاق واسع. باستخدام مجموعات بيانات الأقمار الصناعية المستشعرة عن بعد، فحصت الدراسة تغييرات الخط الساحلي من عام 2000 إلى عام 2021 ووجدت مثل هذه التفاوتات في تغييرات الخط الساحلي طوال السنوات الـ 21 السابقة. كما تم حساب معدلات التآكل والتراكم. باستخدام العديد من الملفات الشخصية، والتي يعبر كل منها عن معدل تآكل أو ترسيب الساحل، تم استخدام أداة نظام تحليل الخط الساحلي الرقمي لتحديد أنماط تغير الخط الساحلي. وفقًا للنتائج، كان غرب موقع البحث لديه معدل تآكل مرتفع، بينما كان شرقه لديه معدل ترسيب مرتفع. وفي منطقة الخمس الوسطى كانت النسبتان متساويتين، ووفقاً للنتائج فإن نسب الترسيب كانت أعلى من نسب مناطق الدراسة باستثناء جزيرة باسيس حيث كانت نسب التعرية أعلى، وقد تكون النسب المحسوبة في هذه الدراسة وتصنيف شواطئ موقع الدراسة مفيدة جداً في تحديد الأثر التراكمي ومخاطر التعرية للمناطق الساحلية قيد الدراسة، وكذلك في وضع خطط التنمية المستدامة لها ورفع الوعي في المناطق الأكثر عرضة للخطر